2011
DOI: 10.1007/s10719-011-9337-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycan structures of the structural subunit (HtH1) of Haliotis tuberculata hemocyanin

Abstract: The oligosaccharide structures of the structural subunit HtH1 of Haliotis tuberculata hemocyanin (HtH) were studied by mass spectral sequence analysis of the glycans. The proposed structures are based on MALDI-TOF-MS data before and after treatment with the specific exoglycosidases β1-3,4,6-galactosidase and α1-6(>2,3,4) fucosidase followed by sequence analysis via electrospray ionization MS/MS-spectra. In total, 15 glycans were identified as a highly heterogeneous group of structures. As in most molluscan hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…An ␣-galactoside was specifically recognized by MytiLec in FACT analysis, although the occurrence of these sugars in mussels is not yet clear. Certain Gal-containing oligosaccharides in glycoproteins have been recently found in some mollusks by mass spectrometric analysis (55)(56)(57). MytiLec was obtained together with the haptenic saccharide Gal and therefore bound to mussel tissues.…”
Section: Discussionmentioning
confidence: 99%
“…An ␣-galactoside was specifically recognized by MytiLec in FACT analysis, although the occurrence of these sugars in mussels is not yet clear. Certain Gal-containing oligosaccharides in glycoproteins have been recently found in some mollusks by mass spectrometric analysis (55)(56)(57). MytiLec was obtained together with the haptenic saccharide Gal and therefore bound to mussel tissues.…”
Section: Discussionmentioning
confidence: 99%
“…FLH is composed of a single type of subunit that forms homodidecamers (8). Another significant feature of the hemocyanin structure is the presence of carbohydrates, as heterogeneous N-and O-glycosylation ramifications, with mannose being the common and most abundant oligosaccharide (25)(26)(27)(28)(29)(30). Although the three hemocyanins present N-and O-linked oligosaccharides, there are differences in their arrangements.…”
mentioning
confidence: 99%
“…It is known that hemocyanins are glycosylated (20,44,45), and some of the important features of hemocyanins in clinical applications such as immunogenicity and antigenicity are related to their high carbohydrate content and unusual glycans (46)(47)(48). Furthermore, Dolashka-Angelova et al (20) demonstrated that one functional unit (50 kDa; the building blocks of hemocyanin) of Rapana thomasiana hemocyanin that was natively devoid of glycans lacked antiviral activity against poliovirus type 1.…”
Section: Discussionmentioning
confidence: 99%